STUDENTS' LEARNING INTEREST IN THE IMPLEMENTATION OF PROJECT-BASED LEARNING MODELS - Yohanes Bery Mokalu; Meike Paat; Ester Caroline Wowor; Widya Anjelia Tumewu; Femmy Roosje Kawuwung (SOSCIED, 2023)
This research aims to investigate students' interest in learning through the project-based learning model. The study was conducted at the Department of Biology Education and the Department of Science Education at Manado State University. The research method employed was quantitative descriptive. The subjects consisted of 20 students participating in project-based learning in the instructional media course. Data were collected through a learning interest questionnaire distributed at the end of the semester and measured using a Likert scale. The results indicated that for 12 statement items, the percentage fell within the range of 81%-100%, indicating a high level of interest among all respondents. Therefore, it can be concluded that the implementation of the project-based learning model effectively stimulates and optimizes students' learning interest.